Pengaruh Macam dan Konsentrasi Ekstrak Tomat Terhadap Pertumbuhan Anggrek Cattleya Secara In Vitro - Barroroh, Umul; Aiman, Umul (Universitas Muhammadiyah Yogyakarta, 2005)
The research was aimed to observe the influence of kinds and dosage of tomato extract on growth of orchid Cattleya planlet in the Murashige and Skoog media. The experiment was arranged in a completely random design (2 x 3) + 1 control with three replications. The first factor was maturity of tomato consisted of 2 levels i.e riped and green tomato. The second factor was dosage of tomato extract consisted of 100 gram/liter, 150 gram/liter, 200 gram/liter, and with no tomato extract as control. Result of the research indicated that application of 100 g/liter of ripening tomato extract gave the better growth of Cattleya orchid than the other treatments.